Boron removal from aqueous solution using curcumin-impregnated activated carbon - Azhar Abdul Halim,; Nor Alia Roslan,; Nor Shamsiah Yaacub,; Mohd. Talib Latif, (Universiti Kebangsaan Malaysia, 2013)
This study was conducted to investigate the batch and fixed-bed adsorption properties of boron on curcumin-impregnated activated carbon (Cur-AC). The maximum boron removal was obtained at pH5.5 and 120 min of contact time. Langmuir and Freundlich isotherm models were applied and it was determined that the experimental data conformed to both models. The Langmuir maximum adsorption capacities for Cur-AC (5.00 mg/g) and regenerated Cur-AC (3.61 mg/g) were obviously higher than the capacity for bare activated carbon (0.59 mg/g). Kinetic studies indicated the adsorption of boron conformed to the intra-particle model. The highest boron removal in fixed-bed column adsorption was achieved up to 99% for the first 5 min at an inlet concentration of 890 mg/L and a flow rate of 8.0 mL/min. Thomas and the Yoon-Nelson models gave better fit to the experimental data. Cur-AC can be reused after elution processes with slightly lower adsorption capacity.